2007
DOI: 10.2355/isijinternational.47.299
|View full text |Cite
|
Sign up to set email alerts
|

Transformation in Stir Zone of Friction Stir Welded Carbon Steels with Different Carbon Contents

Abstract: Five types of ferrite-pearlite structure carbon steels with different carbon contents (IF steel, S12C, S20C, S35C, S50C) were friction stir welded under various welding conditions, and the mechanical properties and microstructures of the FSW carbon steel joints were evaluated. Compared with IF steel, the microstructures and mechanical properties of the carbon steel joints are significantly affected by the welding conditions. When the carbon content is less than or equal to 0.12 mass%, the welding produces ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 18 publications
(16 reference statements)
2
36
1
3
Order By: Relevance
“…In recent years, the advances in the tool materials have improved their durability and enabled the welding of steels in a laboratory scale. A number of studies have been reported on the FSW of steels, such as the interstitial free (IF) steel, 4) carbon steels [5][6][7][8][9] and stainless steels. [10][11][12][13] Some of them especially detailed the FSW process for ferrous materials, investigating the influence of the thermal history and the carbon content on the microstructures of the welds.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the advances in the tool materials have improved their durability and enabled the welding of steels in a laboratory scale. A number of studies have been reported on the FSW of steels, such as the interstitial free (IF) steel, 4) carbon steels [5][6][7][8][9] and stainless steels. [10][11][12][13] Some of them especially detailed the FSW process for ferrous materials, investigating the influence of the thermal history and the carbon content on the microstructures of the welds.…”
Section: Introductionmentioning
confidence: 99%
“…2.2.1 페라이트계 강 페라이트계 강에 대한 FSW 보고는 지금 까지 연강 8) , 각종 탄소강 [9][10][11][12][13][14] , DH36강 15) , C-Mn강 16,17) , 라인 파이 프용강 18,19) , 12%Cr강 20,21) , HSLA-65강 [22][23][24][25][26] , DP강 [27][28][29][30] , B첨가강 . 그러나 접합조건을 조절하여 냉 각속도 및 최고도달온도를 제어하면 FSW후 경화조직 의 형성을 억제할 수 있다 [10][11] .…”
Section: 철강재 Fsw접합부 특성unclassified
“…Cui et al 19) have reported that the martensitic transformation occurs in the carbon steels during FSW at the high travel speeds. The 0.5 % C steel experienced the martensitic transformation at the rotational speed of 400 rpm during cooling cycle of FSW when the travel speed was higher than 0.42-0.83 mm/s (25-50 mm/min).…”
Section: Microstructure In the Centralmentioning
confidence: 99%
“…31,32) Hardness of the martensitic structure formed in 1.0 % C steels has been reported to be about 850 HV, 31,32) which is roughly the same as that in the central zone. Cui et al 19) have shown that the hardness in the weld depends on the martensite fraction and the hardness of the martensite in carbon steels when the martensite is formed. This situation suggests that the high hardness in the central zone can be attributed to the martensitic structure.…”
Section: Hardness Profilementioning
confidence: 99%
See 1 more Smart Citation